The readiness of teacher candidates for vocational high school in the 4th industrial era viewed from teaching skill and capability in technology - Susanti Susanti; Harti Harti; Vivi Pratiwi (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
This study aims to evaluate the readiness of prospective teachers for Vocational High Schools in dealing with the world of work in the 4th industrial era when viewed from teaching skills and technological mastery abilities. This study is evaluative research with a quantitative descriptive approach. The population in this study consisted of 1,725 students at Universitas Negeri Surabaya. A total of 996 students were used as research samples by using a simple purposive sampling technique. The results show that the average readiness in the aspects of teaching skills as much as 81.78% of students said they are ready, while the average readiness in the aspect of mastering technology is 88.59% so that it can be stated that students as prospective VHS teachers are very ready to face the world of work. Vocational teacher candidates already have good teaching skills because they are equipped with various theories and practices directly to the school, from skills to close the open lesson, even drafting learning lessons so that they have the experience they are prepared to use in the world of work. In the ability to master technology, vocational teacher candidates already have a good readiness to use technology in learning, such as accessing various Microsoft programs.